2015
DOI: 10.1007/s00221-015-4493-4
|View full text |Cite
|
Sign up to set email alerts
|

The Attention Network Test-Interaction (ANT-I): reliability and validity in healthy older adults

Abstract: The Attention Network Test (ANT) is a frequently used computer-based tool for measuring the three attention networks (alerting, orienting, and executive control). We examined the psychometric properties of performance on a variant of the ANT, the Attention Network Test-Interaction (ANT-I) in healthy older adults (N = 173; mean age = 65.4, SD = 6.5; obtained from the Brain in Motion Study, Tyndall et al. BMC Geriatr 13:21, 2013. doi: 10.1186/1471-2318-13-21) to evaluate its usefulness as a measurement tool in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 31 publications
5
27
0
3
Order By: Relevance
“…The absence of alerting effects on visual attention capacity in the older group lends support to the notion that the LC-NE system is affected by aging (e.g., Lohr & Jeste, 1988;Manaye, McIntire, Mann, & German, 1995;Mather & Harley, 2016;Vijayashankar & Brody, 1979). Presumably, deficient NE signalling mitigated the responsiveness to the warning cues (Coull et al, 2001;Oberlin, Alford, & Marrocco, 2005;Witte & Marrocco, 1997), and attenuated or even abolished the phasic alerting effect in the older group (see Ishigami et al, 2016). More specifically, our results suggest that this deficit has already affected early visual processing stages: albeit numerically, the alerting effect on ERLs in the older group was not entirely absent, but clearly reduced compared to the younger group.…”
Section: Age-related Changes In the Network Of Alertness And Attentionsupporting
confidence: 55%
See 1 more Smart Citation
“…The absence of alerting effects on visual attention capacity in the older group lends support to the notion that the LC-NE system is affected by aging (e.g., Lohr & Jeste, 1988;Manaye, McIntire, Mann, & German, 1995;Mather & Harley, 2016;Vijayashankar & Brody, 1979). Presumably, deficient NE signalling mitigated the responsiveness to the warning cues (Coull et al, 2001;Oberlin, Alford, & Marrocco, 2005;Witte & Marrocco, 1997), and attenuated or even abolished the phasic alerting effect in the older group (see Ishigami et al, 2016). More specifically, our results suggest that this deficit has already affected early visual processing stages: albeit numerically, the alerting effect on ERLs in the older group was not entirely absent, but clearly reduced compared to the younger group.…”
Section: Age-related Changes In the Network Of Alertness And Attentionsupporting
confidence: 55%
“…Previous behavioural investigations on phasic alerting in aging have yielded inconsistent results. Some studies have reported preserved or even increased phasic alerting in older compared with younger adults (Fernandez-Duque & Black, 2006;Nebes & Brady, 1993;Rabbitt, 1984), while other studies have shown decreased or absent alerting effects in older age (e.g., Festa-Martino, Ott, & Heindel, 2004;Gamboz, Zamarian, & Cavallero, 2010;Ishigami et al, 2016;Jennings, Dagenbach, Engle, & Funke, 2007;Zhou, Fan, Lee, Wang, & Wang, 2011). The diversity of findings has been suggested to result from variations in the sensory, cognitive, and motor components involved in a given task.…”
mentioning
confidence: 99%
“…While such effects are consistently reported in younger samples, examinations of older adults are inconclusive: Some have reported preserved effects (Fernandez-Duque and Black, 2006;Haupt et al, 2018;Rabbitt, 1984), while others have shown decreased or even absent alerting effects in older age (e.g., Festa-Martino et al, 2004;Gamboz et al, 2010;Ishigami, et al, 2016;Wiegand, Petersen, Bundesen et al, 2017). The mechanisms underlying age-related decline in alerting may be elusive if age differences in processing of the alert itself are investigated in samples in which no benefit from the cue was observed (Wiegand, Petersen, Bundesen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent versions of the ANT also allow an assessment of the interactions among the attention networks (ANT-Interactions, Callejas et al, 2005 ; ANT-Revised, Fan et al, 2009 ). The ANT and ANT-I have been used in a variety of populations, including children, healthy adults of varying ages, and a variety of clinical populations and allow for comparisons across attentional networks due to their integrated nature and brevity (Fernandez-Duque and Black, 2006 ; Adolfsdottir et al, 2008 ; AhnAllen et al, 2008 ; Ishigami and Klein, 2010 ; Ishigami et al, 2016 ; see review in MacLeod et al, 2010 ). While use of the ANTs has proved valuable for exploration of attention mechanisms in normal and clinical populations, there are limitations to these tests.…”
Section: Introductionmentioning
confidence: 99%
“…In order to limit test time, the assessment of alerting, orienting, and executive control is dependent upon a single difference measure producing a network score, with alerting and orienting network RT scores showing lower than ideal reliability across studies (ranging from 0.20 to 0.61) and the executive network RT score showing better reliability (ranging from 0.65 to 0.81; Fan et al, 2002 ; MacLeod et al, 2010 ). In addition, investigations of the validity of the ANT are limited, but Ishigami et al ( 2016 ) found that while the executive network score was a significant predictor of conflict resolution, and verbal memory retrieval, no associations were found between the alerting and orienting network scores and other standardized tests of attention. Likewise, comparisons between the ANT and an assessment based on TVA also yielded no significant correlations (Habekost et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%